2019
DOI: 10.3389/fendo.2018.00766
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism Disrupting Chemicals and Alteration of Neuroendocrine Circuits Controlling Food Intake and Energy Metabolism

Abstract: The metabolism-disrupting chemicals (MDCs) are molecules (largely belonging to the category of endocrine disrupting chemicals, EDCs) that can cause important diseases as the metabolic syndrome, obesity, Type 2 Diabetes Mellitus or fatty liver. MDCs act on fat tissue and liver, may regulate gut functions (influencing absorption), but they may also alter the hypothalamic peptidergic circuits that control food intake and energy metabolism. These circuits are normally regulated by several factors, including estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 122 publications
(138 reference statements)
0
30
0
Order By: Relevance
“…The sexual dimorphic response specific to ER action has been associated with the development of or protection from certain diseases (e.g., metabolic syndrome and autoimmune diseases) [33][34][35][36]. As such, animal studies have demonstrated that exogenous exposures that inappropriately alter ER signaling can increase the relative risk for these diseases [37][38][39]. To determine whether the genetic sex of a cell could influence the transcriptional response to the xenoestrogens, we repeated our analysis of differentially expressed genes in HepaRG cells, which were derived from the liver of a female patient [40].…”
Section: The Role Of Genetic Sex In Mediating the Cellular Response Tmentioning
confidence: 99%
“…The sexual dimorphic response specific to ER action has been associated with the development of or protection from certain diseases (e.g., metabolic syndrome and autoimmune diseases) [33][34][35][36]. As such, animal studies have demonstrated that exogenous exposures that inappropriately alter ER signaling can increase the relative risk for these diseases [37][38][39]. To determine whether the genetic sex of a cell could influence the transcriptional response to the xenoestrogens, we repeated our analysis of differentially expressed genes in HepaRG cells, which were derived from the liver of a female patient [40].…”
Section: The Role Of Genetic Sex In Mediating the Cellular Response Tmentioning
confidence: 99%
“…Several studies carried out in both humans and animals have shown that EDCs restrain the androgen receptor pathway, augment, or block the estrogen pathway, and/or decrease androgen levels through the up-regulation of the aromatase enzyme. These hormonal modifications lead to an increased number and size of adipose cells, altered adipocytokine production, reduction of basal metabolic rate, and modification of appetite and satiety signaling (85). Although the available data derived from animal studies are more solid than those obtained from human epidemiological studies, a link between EDCs and an adverse metabolic profile is predicted.…”
Section: Synthesis Of Datamentioning
confidence: 99%
“…The hypothalamus in the central nervous system plays an essential role in the modulation of appetite and energy expenditure. Compromised hypothalamus regulation is involved in the development of obesity (Carmo-Silva and Cavadas, 2017;Marraudino et al, 2019;Seong et al, 2019). However, the effect of sleep curtailment on the regulation of appetite in the hypothalamus and the mechanisms underlying this are not fully understood and need further exploration.…”
Section: Introductionmentioning
confidence: 99%